Peningkatan Kesehatan Anak Usia Dini dengan Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) di TK Kecamatan Candi Sidoarjo - Choirun Nisak Aulina; Yuli Astutik (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
The purpose of this community service is to increase the knowledge of teachers and parents about the importance of Clean and Healthy Behaviour (PHBS). Clean and healthy behavior is also a set of behaviours practiced by learners, teachers and the school environment community on the basis of awareness so that independently able to prevent disease, improve health, and play an active role in creating a healthy environment. This community service activity is carried out in kindergarten of Aisyiyah 6 and kindergarten of Riadhus Sholihin at Kecamatan Candi Sidoarjo. The Method used in implementing this community service undertaken to solve the existing problems for those partner schools, such as 1) Workshop on integrating the implementation of Clean and Healthy Behaviour (PHBS) in learning activities, 2) parenting activities about healthy food for children. The result of this community service activity is a school regulation which contains about eight indicators of school PHBS implementation, scheduling five supporting activities of school PHBS implementation, and children not snacking haphazardly.